Optimasi Hybrid Invisible Watermarking RDWT-DCT-SVD menggunakan Algoritma PSO pada Citra Digital - -, nendi -; Januar Insani, Oki; Nugraha Abdullah, Indra (Jurnal Teknologi Terpadu, 2020)
It is now so easy in this digital age to duplicating and distributing any information, particularly in image data which makes some people using it for negative purposes because by using false image information, indeed violates intellectual property rights from data ownership. The Watermarking method is one of many approaches to copyright protection. There are several ways to apply watermarking, one of them is a hybrid invisible watermark. Research that has been done by Anu Bajaj in 2013 which combining RDWT-DCT-SVD techniques by proving the results of its efficiency with PSNR values for different attacks. However, on its research advice told watermarking hybrid is not safe, so on the next research, it is recommended to increase the security in the form of optimization in terms of inserting information into the input image, in order to improve PSNR assessment scheme which is sufficiently safe and higher. The goal of this research is the author adding the PSO algorithm to be combined with its hybrid technique with the intention of providing security in terms of inserting and giving improvement on the PSNR scheme. By this analysis result, examination and comparison can be concluded that hybrid invisible watermarking, RDWT-DCT-SVD with PSO optimizing have significantly higher results that have means 50 dB, so this has better imperceptibility quality..